The Uninsured Drivers’ Agreement 2015 as a legitimate source of authority - Marson, James; Ferris, Katy (Oxford University Press, 2016)
In the United Kingdom, motor vehicle insurance is governed by national and EU law. In respect of the EU requirement that member states establish a guarantee fund from which the victims of negligent uninsured or untraced drivers may obtain compensation, the United Kingdom entered into a series of agreements with the Motor Insurers’ Bureau (MIB). In 2015, the MIB established the Uninsured Drivers’ Agreement (UDA). This agreement implements (with the Road Traffic Act 1988 and the Untraced Drivers’ Agreement 2003) aspects of the Motor Vehicle Insurance Directives (MVID). The UDA 2015 establishes clauses and procedural arrangements which, we argue, have largely removed legal certainty for policyholders and for the victims of negligent uninsured drivers. As such, the fundamental goals of the MVID and the free movement principles upon which they are based are undermined in the United Kingdom. This article offers a critique of the substantive breaches of the MVID through the UDA 2015’s exclusions and procedural arrangements and identifies the current state of unpredictability and uncertainty when the two sources of law are compared.